Cadmium pollution in seafood, Lima - 2015 - Marín, Gloria M. (2017)
In the present investigation, cadmium concentrations in seafood were determined and compared with the maximum levels of Commission of the European Union in its Regulation (EC) Nº 1881/2006 and amending Regulation (EU) No 488/2014. Samples were collected from the fish market of Villa Maria del Triunfo. Analyses were performed by atomic absorption spectrophotometry. The results were: in fish (horse mackerel: Trachurus picturatus murphyi) the average cadmium concentrations was 0,35 mg/kg fresh weight, well above the allowable value which is 0,05 mg/kg fresh weight. In crustaceans (prawns: Litopenaeus vannamei) the average was 0,42 mg/kg fresh weight, being below the maximum allowed limit which is 0,50 mg/kg fresh weight. The ceiling in bivalve molluscs is 1,00 mg/kg fresh weight and different concentrations were found in different species and in white shells (Semele sp) and scallops (Argopecten purpuratus) do not exceed the permitted limits; the mussels (Aulacomya atra) are borderline; the machas (Mesodesma donacium) and clams (Gari solida) exceed the limit values. Finally, cephalopods (giant squid: Dosidicus gigas) the average was 1,11 mg/kg fresh weight, being slightly higher than the allowable limit 1,00 mg / kg fresh weight.